Molecular Aspects of Colorectal Cancer Prognosis in 10 years (Nusantara Science and Technology Proceedings, 2022)
Colorectal cancer (CRC) ranks third in the world with an increasing mortality rate, prompting an analysis of various studies that have been conducted over the last 10 years. The inclusion criteria of the analyzed research articles were studies involving the molecular aspects of colorectal cancer associated with its prognosis in the last 10 years. The international literature search method was carried out through article data published in Embase, Scopus, and PubMed using keywords: colorectal cancer, molecular aspects, and prognosis. Through the 440 articles found during the first search out, after going through the final selection stage, 29 articles were determined that met the inclusion criteria. The research method that is widely used in the research analyzed is immunohistochemistry accompanied by PCR. Various molecular aspects have been found to play a role in determining carcinogenesis, response to therapy, and the prognosis of CRC. They generally examine aspects of genes and progress towards microRNA and some molecular aspects are still useful in determining the prognosis so they are still being worked on at this time but further research is needed to further complement the existing data about CRC.